International Digital Transformation of Smart MSMEs for Sustainable Business Development - Indra Hastuti; Maimunah Abdul Aziz (International Forum of Researchers and Lecturers, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia and Malaysia constitute the core drivers of employment and economic growth, yet many remain constrained by limited competitiveness in international markets due to uneven digital adoption. This study addresses the problem of how international digital transformation can be effectively leveraged to enhance the performance and sustainability of Smart MSMEs, with the objective of identifying key digital strategies that support sustainable business development. Employing a mixed-methods approach, the research combines quantitative surveys of MSME actors with qualitative in-depth interviews of business owners who have implemented international digital initiatives, including cross-border e-commerce, global payment systems, and international digital marketing. The data are analyzed using descriptive and comparative techniques to examine enabling factors, challenges, and cross-country differences between Indonesia and Malaysia. The findings indicate that international digital transformation significantly improves market access, operational efficiency, and business resilience, while strategic integration of digital platforms and international networks strengthens long-term sustainability. The study concludes that developing Smart MSMEs through internationally oriented digital transformation is a critical pathway for achieving sustainable business development and enhancing regional and global competitiveness, and it offers strategic and policy-oriented recommendations for MSME stakeholders.